Collector ring project at FAIR. (26th November 2015) - Dolinskii, A; Berkaev, D; Blell, U; Dimopoulou, C; Gorda, O; Leibrock, H; Litvinov, S; Laier, U; Koop, I; Schurig, I; Starostenko, A; Shatunov, P; et al.
Abstract: The collector ring is a dedicated ring for fast cooling of ions coming from separators at the FAIR project. To accommodate optimal technical solutions, a structure of a magnet lattice was recently reviewed and modified. Consequently, more appropriate technical solutions for the main magnets could be adopted. A general layout and design of the present machine is shown. The demanding extraction schemes have been detailed and open design issues were completed.